Pengembangan Media Poster Berbasis Pictorial Riddle Model 4D Sebagai Bahan Ajar Mata Kuliah Pendidikan Agama Program Studi Pendidikan Agama Hindu - Ni Rai Vivien Pitriani; I Gusti Ayu Desy Wahyuni; I Ketut Bali Sastrawan (Jayapangus Press, 2023)
The purpose of this study was to determine the development of 4-D pictorial riddle-based poster media as teaching materials for religious education courses in the Hindu Religious Education Study Program; find out whether poster media is feasible or not to be used based on the assessment of material experts, learning practitioners and media experts; knowing the interest in learning and student learning outcomes after using poster media. This type of research and development refers to the 4D model of the development process. At the development stage (Develop) learning tools, all the instruments used and the poster media developed were validated by learning experts and practitioners. Expert validators and practitioners are Lecturers of STAHN Mpu Kuturan Singaraja. The develop stage consists of a limited field test and an extensive test. The results showed that Pictorial Riddle-Based Poster Media was developed in four stages, namely Define, Design, Develop, and Disseminate; Pictorial Riddle-based poster media is said to be feasible in terms of SBI, PA (Percentage of Agreement) scores, and based on the results of student response questionnaires. The poster media has an SBI score of 3.92 in the good category, the PA score is 92.2%, and the result of the student response questionnaire is 3.86 in the good category and is included in the appropriate category for use. Based on the normalized gain value, the increase in student interest in the second semester of the Hindu Religious Education Study Program after applying the poster media is 0.13 with a low significant level. Based on the normalized gain value, the increase in student learning outcomes in the second semester of the Hindu Religious Education Study Program after applying the poster media was 0.42 with a moderate significance level. The results showed that the poster media based on pictorial riddles that was developed was very well used as teaching material in the Hindu Religious Education Study Program.